Chronic shifts in the length and phase of the light cycle increase intermittent alcohol drinking in C57BL/6J mice - Gamsby, Joshua J.; Gulick, Danielle (Frontiers in Behavioral Neuroscience, 2015)
Introduction: Shift workers – e.g., health care professionals, truck drivers, and factory workers – are forced to maintain daily cycles at odds with their natural circadian rhythms and as a consequence need to frequently readjust these cycles. This shift work-induced circadian desynchrony (CD) is associated with increased sleep disorders and with alcohol abuse. Nonetheless, it has proven difficult to model CD-induced changes in alcohol consumption in mouse models, which is an important step toward identifying the mechanisms by which CD increases alcohol intake. This study examined whether frequent changes in the light cycle could increase free access alcohol intake in a mouse line that readily consumes alcohol. Methods: Free access alcohol intake, water intake, and wheel-running activity patterns of male C57BL/6J mice were measured while the mice were maintained on a normal 12HR photoperiod for baseline data for two weeks. The mice were then exposed to an alternating photoperiod of 12 hours and 18 hours, with light onset advanced 8 hours during the 18HR photoperiod. The photoperiods rotated every three days, for 21 days total. Results: The repeated pattern of phase advances and delays, with a concurrent change in the length of the photoperiod, shifted mice to a pattern of bingeintermittent drinking alcoholalcohol drinking without altering water intake. Wheel running activity demonstrated that mice were unable to reset their behavioral clocks during CD, showing constant, low-level activity with no peak in activity at the start of the dark phase and greater activity during the morning light phase. Conclusion: It is possible to model CD effects on alcohol intake in C57BL/6J mice using a pattern of phase shifts and changes in the photoperiod. Using this model, we demonstrate that mice begin intermittent drinking during CD, and this increase in alcohol intake does not correlate with an increase in overall activity or in overall fluid intake.